Markedness in Word-Order Typology of Minangkabaunese - Jufrizal; Lely Refnita; M. Affandi Arianto (ELITE Association Indonesia, 2023)
The typological analyses on word-order typology of Minangkabaunese have been becoming topics of typological studies in some aspects, but those which are based on the markedness theory are still limited. Therefore, the analysis on markedness values of word-order typology of Minangkabaunese is linguistically meaningful. This article, as the development and further discussion of a part of the results of a research conducted in 2020/2021, analyzes and discusses the markedness values of word-order typology of Minangkabaunese. There are two questions to be answered in this paper: (i) what are the word-word order typology of Minangkabaunese?; and (ii) what is the markedness value of each word-order typology of Minangkabaunese? The data analysis and discussion are based on the related theories of word-order typology and markedness developed and used in Grammatical Typology. The data presented in this paper are the clause constructions which were collected by means of a descriptive-qualitative research and practically executed as of a field research in West-Sumatera and supported by a library study. The result of data analysis reveals that there are three productive patterns of grammatical constructions in Minangkabaunese identified as SVO, VOS, and OSV. However, there are only two patterns of the three grammatical-clause constructions that can be assigned as the basic word-order typology in this local language, namely: SVO and VOS. Therefore, the basic clause constructions with SVO and VOS word-order are unmarked meanwhile those with OSV word-order are marked ones. Furthermore, the markedness value of SVO is higher than that of VOS. In hierarchy, the markedness value of the three productive grammatical constructions in Minangkabaunese can be formulated as: SVO < VOS < OSV. This grammatical-typological analysis contributes to the more specific description of grammatical properties of Minangkabaunese as one of main local languages in Indonesia. Keywords: grammatical-typol